Speculative machines and us: more-than-human intuition and the algorithmic condition. - Pedwell, Carolyn (Cultural Studies, 2024)
In the wake of Turing's 'universal machine', this article foregrounds intuition as a generative concept and lens to unfold the affective genealogies of human-machine relations in post-war transatlantic cultures. As a mode of sensing, knowing, anticipating, and navigating the world that exceeds rational analysis, intuition is, I will argue, vital to attuning to our contemporary 'algorithmic condition', in which machine learning technologies are actively re-distributing cognition across humans and machines, transforming the nature of (in)human experience, and rearticulating questions of cultural value and desire. The article focuses on three key historical moments which enable us to retrospectively glimpse an emerging condensation of interest and urgency concerning our changing relationships with 'new' technologies in Britain and North America – 1) 1950s: The birth of AI and cybernetics; 2) 1980s: The rise of the personal computer and software cultures and; 3) 2010s: Inhabiting algorithmic life. In each period, particular aspects of intuition surface as significant in animating our affective and cultural entanglements with computational technologies. While intuition has gained affective traction at particular historical junctures as both what essentially defines 'the human' and what has become essentially inhuman, I argue that addressing the sensorial, socio-political, cultural, and ethical issues current machine learning architectures open up requires attuning to immanent human-algorithmic entanglements and the techno-social ecologies they inhabit and recursively reshape.